Performance relationships in timed and mass-start events for elite omnium cyclists - Phillips, K. E.; Hopkins, W. G. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To explore the extent to which factors that determine performance transfer within and between time-trial and mass-start events in the track-cycling Omnium.